Utvärdering av traktplanering på Holmen Skog - Fahlén, Emil (SLU/School for Forest Management, 2012)
This study has been performed with the help of forest machine operators in order to improve the forestry planning at Holmen Skog Örnsköldsvik-region. For Holmen Skog forestry planning is basic for a successful forestry. In a survey I have investigated what can be improved in some areas that are planned for harvesting. The result of the investigation will be used to support the machine operators as much as possible. The study has generated 49.5 % of responses and because of this low response rate, no clear conclusions to anyone else except the responding machine operators can be drawn. It has been proved that there are some details in the forestry planning system that are inadequate, such as marked routs for trails, tractor paths and buffer zones against streams. The quality of forestry planning varies greatly between different locations, as much as 50 % of the responding machine operators thought so. Over 40 % of the responding machine operators claim that the information from Holmen is insufficient. One thing that would improve the forestry planning within Holmen would be to educate all forestry planners and then do continuous follow-ups.